Colon cancer pharmacogenetics: A narrative review - Alfaro Alfaro, Álvaro Esteban (2022)
Currently, metastatic colon cancer is treated with monotherapeutic regimens such as folinic acid, fluorouracil, and oxaliplatin (FOLFOX), capecitabine and oxaliplatin (CapeOX), and leucovorin, fluorouracil, and irinotecan hydrochloride (FOLFIRI). Other treatments include biological therapies and immunotherapy with drugs such as bevacizumab, panitumumab, cetuximab, and pembrolizumab. After the research, it was found that some mutations make those treatments not as effective in all patients. In this bibliographic review, we investigated the pharmacogenetic explanations for how mutations in the genes coding for rat sarcoma virus (RAS) and rapidly accelerated fibrosarcoma (RAF) reduce the effectiveness of these treatments and allow the continued proliferation of tumors. Furthermore, we note that patients with mutations in the dihydropyrimidine dehydrogenase (DPDY) gene usually require lower doses of therapies such as 5-fluorouracyl (5-FU) and capecitabine to avoid severe adverse effects. Some other mutations in the thymidylate synthase gene (TSYM), methylenetetrahydrofolate reductase gene (MTHFR), and ATP binding cassette transporter B (ABCB1 and ABCB2) affect efficacy and security of the treatments. It is important to address the clinical implication of the oncologist in the study of gene mutations than can influence in the antitumoral response and safety of colon cancer treatments.